Monorail extrusion welding process of novel geomembrane
The monorail extrusion welding process for geomembrane addresses the adaptability and weldability issues of HDPE geomembranes by using a novel TPO and HDPE combination with an anti-ultraviolet layer, ensuring stable performance and effective anti-seepage in reservoirs.
Patent Information
- Application Number
- CN202411431505.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-14
AI Technical Summary
HDPE geomembranes with a thickness of more than 1.0 mm are too hard and have poor ability to adapt to foundation deformation, leading to tensile damage and concentrated leakage in reservoirs due to differential displacement.
A monorail extrusion welding process for geomembrane using TPO geomembrane, new geomembrane, and HDPE geomembrane, with a novel substrate and anti-ultraviolet layer, welded by a single-track extrusion welding machine, and prepared with specific material ratios and coating processes to enhance deformation adaptability and weldability.
The process ensures stable geomembrane performance, prevents damage, improves construction efficiency, and provides a reliable anti-seepage barrier, extending the geomembrane's service life and protecting groundwater resources.
Smart Images

Figure BDA0005083796120000101 
Figure BDA0005083796120000111
Abstract
Description
Technical Field
[0001] The present application relates to a novel monorail extrusion welding process for geomembrane, belonging to the technical field of geomembrane construction. Background Art
[0002] Anti-seepage construction in reservoir areas is a key link in the fields of water conservancy projects, environmental protection projects, construction projects, etc. Its purpose is to prevent water, chemicals or pollutants from penetrating into the soil, thereby protecting the safety of groundwater resources and the surrounding environment. In this field, geomembrane construction technology has become an important and indispensable engineering practice due to its outstanding anti-seepage effect, long-term stability and engineering economy.
[0003] High-density polyethylene (HDPE) geomembrane has the advantages of good durability, large width, fast construction speed and low project cost. However, engineering practice has found that HDPE geomembranes with a thickness of more than 1.0 mm are too hard and have poor ability to adapt to foundation deformation. The large differential displacement between the anchoring parts of the structure can easily cause tensile damage, which in turn leads to concentrated leakage of the reservoir. Summary of the invention
[0004] In order to solve the above problems, a new type of monorail extrusion welding process for geomembrane is provided, which is easy to construct. The new type of geomembrane used has both the excellent deformation adaptability of elastic materials and the weldability of plastic materials. When used for reservoir seepage control, it can avoid leakage and damage at the connection parts of the reservoir bottom.
[0005] The present invention adopts the following technical solutions:
[0006] A new type of monorail extrusion welding process for geomembrane, including:
[0007] (1) The bottom surface of the reservoir is leveled to ensure that there are no impurities within a vertical depth of 20-25 mm, and then the bottom surface is dried to ensure that the moisture content of the bottom does not exceed 15%;
[0008] (2) According to the reservoir bottom conditions, cut the geomembrane into appropriate sizes, then lay the stretched geomembrane on the reservoir bottom surface and keep the overlap area flat;
[0009] (3) The TPO geomembrane, the new geomembrane and the HDPE geomembrane are overlapped in sequence and welded by a single-track extrusion welding machine so that the intersections formed between the membrane blocks are T-shaped;
[0010] (4) Testing the TPO geomembrane, new geomembrane and HDPE geomembrane welded in step (3), and marking and repairing the defective parts found until they are retested and qualified;
[0011] The novel geomembrane comprises a substrate layer and an anti-ultraviolet layer coated on the upper surface of the substrate layer, and the thickness ratio of the substrate layer to the anti-ultraviolet layer is 1:(0.1-0.5).
[0012] Optionally, in step (3), the welding temperature is 350-420° C. and the welding speed is 2-3 m / min.
[0013] Optionally, in step (3), the overlap width is 10-12 cm.
[0014] Optionally, the thickness ratio of the TPO geomembrane, the new geomembrane and the HDPE geomembrane is (1-1.8):1:(1-1.5).
[0015] Optionally, the novel geomembrane is prepared by the following method:
[0016] a. By weight, 15-20 parts of polyetheretherketone, 10-16 parts of polycarbonate, 8-13 parts of modified polyester fiber, 6-11 parts of boron nitride, 30-45 parts of high-density polyethylene, 25-32 parts of low-density polyethylene, 20-27 parts of linear low-density polyethylene, 15-25 parts of polyethylene and 12-18 parts of ethylene-octene copolymer are placed in a twin-screw extruder at a main engine speed of 50-60 rpm, and calendered after extrusion through a die at 170-180° C. to obtain a substrate layer;
[0017] b. Dispersing nano-SiO2 in a mixed solution of distilled water and anhydrous ethanol, adding 3-7% silane coupling agent and stirring evenly to obtain a nano-SiO2 aqueous solution, dissolving polyvinyl alcohol in distilled water to obtain a polyvinyl alcohol aqueous solution, mixing the polyvinyl alcohol aqueous solution and the nano-SiO2 aqueous solution, placing in a water bath and stirring for 20-40 minutes, placing in an ultrasonic water tank and ultrasonically dispersing for 20-40 minutes, filtering, and obtaining an anti-ultraviolet layer coating;
[0018] c. Applying the anti-ultraviolet coating on the upper surface of the substrate layer to form an anti-ultraviolet layer after drying, thereby obtaining a new geomembrane.
[0019] Optionally, in step b, the weight ratio of nano-SiO2 to polyvinyl alcohol is (0.5-1.2):10.
[0020] Optionally, in step c, the coating amount of the anti-ultraviolet coating on the upper surface of the substrate layer is 180-250 g / m 2 .
[0021] Optionally, in step a, the method for preparing the modified polyester fiber comprises the following steps:
[0022] S1, soaking the polyester fiber in anhydrous ethanol overnight, taking it out and drying it to obtain the pretreated polyester fiber;
[0023] S2, adding dopamine hydrochloride to Tris buffer and stirring evenly to prepare a dopamine solution with a concentration of 1-3 g / L, then soaking the pretreated polyester fiber in the dopamine solution overnight, taking it out, washing it with water, and drying it to obtain a preliminarily modified polyester fiber;
[0024] S3. Stir and mix silane coupling agent and ethanol in a volume ratio of 1:(400-600) at 40-60°C for 1-3h, then add FeCl3 to disperse evenly, then add the initially modified polyester fiber and soak for 1-3h, take out, wash with water, and dry to obtain the modified polyester fiber.
[0025] Optionally, the silane coupling agent is selected from at least one of KH550, KH560, and KH570.
[0026] Optionally, in step S3, the weight of the silane coupling agent is 8-12% of the initially modified polyester fiber.
[0027] In the present application, "TPO" refers to 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0028] The beneficial effects of this application include but are not limited to:
[0029] 1. The monorail extrusion welding process of the new geomembrane of the present application ensures that there are no uneven or sharp objects in the construction area by leveling and drying the surface of the reservoir bottom, avoiding damage to the geomembrane, and can keep the performance of the geomembrane stable during use; according to the soil type, thickness, particle distribution and groundwater level of the reservoir bottom, appropriate geomembrane materials are selected during construction to ensure that they can cope with geological conditions; the overlap method between the membrane blocks of the present application can effectively disperse stress, prevent damage caused by stress concentration, and improve the stability and durability of the engineering structure; by inspecting and protecting the geomembrane after welding, the integrity and anti-seepage performance of the geomembrane are ensured, which helps to extend the service life of the geomembrane.
[0030] 2. The monorail extrusion welding process of the new geomembrane of the present application uses a monorail extrusion welding machine for welding, which has a higher degree of automation and thus helps to improve construction efficiency; by setting an anti-ultraviolet layer, it can not only block the direct exposure of ultraviolet rays to the substrate layer, reducing its aging and degradation rate, but also improve the mechanical properties of the new geomembrane; the welding temperature, welding time and overlap width between adjacent membrane blocks are adjusted according to the type and thickness of the geomembrane to ensure the welding quality.
[0031] 3. The monorail extrusion welding process of the novel geomembrane of the present application, by selecting appropriate raw materials, proportions and processes, enables the novel geomembrane to have excellent anti-seepage effect, mechanical strength and durability, and is suitable for various complex geological and climatic conditions; wherein, after the silane coupling agent reacts chemically with the hydroxyl groups on the surface of nano-SiO2, the number of hydroxyl groups on the surface of nano-SiO2 is reduced, thereby reducing its surface tension and avoiding agglomeration; after adding polyvinyl alcohol, on the one hand, it can achieve effective connection with the organic phase in the substrate layer at the interface, thereby enhancing the bonding between the substrate layer and the anti-ultraviolet layer Strength; on the other hand, the lipophilic part of nano-SiO2 can penetrate into the interior of polyvinyl alcohol, and through entanglement with the polymer chain, nano-SiO2 is better dispersed in polyvinyl alcohol, giving full play to its anti-ultraviolet properties, while increasing the crystallinity of polyvinyl alcohol and making the arrangement of molecular chains more regular. When the anti-ultraviolet layer coating is applied on the substrate layer, the path of gas penetration into the substrate layer is extended, which makes it more difficult for gas to pass through the new geomembrane, further enhancing the anti-seepage performance of the new geomembrane, and providing a reliable anti-seepage barrier for the reservoir bottom, thereby protecting groundwater resources and the environment.
[0032] 4. The monorail extrusion welding process of the novel geomembrane of the present application uses a silane coupling agent and dopamine to synergistically modify the polyester fiber. On the one hand, the hydroxyl group of the silane coupling agent can react with the hydroxyl group and amino group of polydopamine, and the active group of the silane coupling agent can react with the active group of polydopamine with Fe 3+ The formation of complexes allows the fiber surface to be coated with more silane coupling agents. The hydroxyl groups exposed on the fiber surface can chemically bond with the matrix, and the amino-terminal carbon chain can be entangled with the matrix. On the other hand, more silane coupling agents attached can increase the roughness of the fiber surface, which is beneficial to increase the action sites between the fiber and the matrix and enhance the degree of fit between the two without affecting the internal structure of the fiber. Therefore, the interfacial bonding strength between the fiber and the matrix is further improved, so that the fiber can effectively transfer the load, and the interface with the matrix can withstand a larger load. When debonding occurs, there is still a matrix attached to the fiber surface, thereby improving the mechanical properties of the new geomembrane. DETAILED DESCRIPTION
[0033] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0034] If no specific conditions are specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The raw materials or instruments used, if no manufacturer is specified, are all conventional products that can be purchased commercially.
[0035] Example 1
[0036] A new type of monorail extrusion welding process for geomembrane, including:
[0037] (1) The bottom surface of the reservoir is flattened to ensure that there are no impurities within a vertical depth of 20 mm, and then the bottom surface is dried to ensure that the moisture content of the bottom is 10%;
[0038] (2) According to the reservoir bottom conditions, cut the geomembrane into appropriate sizes, then lay the stretched geomembrane on the reservoir bottom surface and keep the overlap area flat;
[0039] (3) TPO geomembrane, new geomembrane and HDPE geomembrane are overlapped in sequence with a lap width of 10 cm, and are welded by a monorail extrusion welder at a welding temperature of 350°C and a welding speed of 2 m / min, so that the intersections formed between the membrane blocks are T-shaped;
[0040] (4) Testing the TPO geomembrane, new geomembrane and HDPE geomembrane welded in step (3), and marking and repairing the defective parts found until they are retested and qualified;
[0041] The novel geomembrane comprises a substrate layer and an anti-ultraviolet layer coated on the upper surface of the substrate layer, and the thickness ratio of the substrate layer to the anti-ultraviolet layer is 1:0.1;
[0042] The thickness ratio of the TPO geomembrane, the new geomembrane and the HDPE geomembrane is 1:1:1;
[0043] The novel geomembrane is prepared by the following method:
[0044] a. By weight, 15 parts of polyetheretherketone, 10 parts of polycarbonate, 8 parts of modified polyester fiber, 6 parts of boron nitride, 30 parts of high-density polyethylene, 25 parts of low-density polyethylene, 20 parts of linear low-density polyethylene, 15 parts of polyethylene and 12 parts of ethylene-octene copolymer were placed in a twin-screw extruder at a main engine speed of 50 rpm, and calendered after extrusion through a die at 170° C. to obtain a substrate layer;
[0045] b. Disperse nano-SiO2 in a mixed solution of distilled water and anhydrous ethanol (the volume ratio of the two is 9:1), then add 3% silane coupling agent KH550 and stir evenly to obtain a nano-SiO2 aqueous solution, dissolve polyvinyl alcohol in distilled water to obtain a polyvinyl alcohol aqueous solution, mix the polyvinyl alcohol aqueous solution and the nano-SiO2 aqueous solution, place in a water bath and stir for 20 minutes, then place in an ultrasonic water tank and ultrasonically disperse for 40 minutes, the weight ratio of nano-SiO2 to polyvinyl alcohol is 0.5:10, and after filtering, an anti-ultraviolet layer coating is obtained;
[0046] c. Apply the anti-ultraviolet coating on the upper surface of the substrate layer. The coating amount of the anti-ultraviolet coating on the upper surface of the substrate layer is 180g / m 2 , after drying, an anti-ultraviolet layer is formed to produce a new type of geomembrane;
[0047] In step a, the preparation method of the modified polyester fiber comprises the following steps:
[0048] S1, soaking the polyester fiber in anhydrous ethanol overnight, taking it out and drying it to obtain the pretreated polyester fiber;
[0049] S2, adding dopamine hydrochloride to Tris buffer and stirring evenly to prepare a dopamine solution with a concentration of 1 g / L, then soaking the pretreated polyester fiber in the dopamine solution overnight, taking it out, washing it with water, and drying it to obtain a preliminarily modified polyester fiber;
[0050] S3. Stir and mix the silane coupling agent KH550 and 95% ethanol in a volume ratio of 1:400 at 40°C for 1 hour, then add FeCl3 to disperse evenly, and then add the preliminarily modified polyester fiber to soak for 1 hour. The weight of the silane coupling agent KH550 is 8% of the preliminarily modified polyester fiber. Take it out, wash it with water, and dry it to obtain the modified polyester fiber.
[0051] Example 2
[0052] A new type of monorail extrusion welding process for geomembrane, including:
[0053] (1) The bottom surface of the reservoir is flattened to ensure that there are no impurities within a vertical depth of 22 mm, and then the bottom surface is dried to ensure that the moisture content of the bottom is 13%;
[0054] (2) According to the reservoir bottom conditions, cut the geomembrane into appropriate sizes, then lay the stretched geomembrane on the reservoir bottom surface and keep the overlap area flat;
[0055] (3) TPO geomembrane, new geomembrane and HDPE geomembrane are overlapped in sequence with a overlap width of 11 cm, and are welded by a single-track extrusion welder at a welding temperature of 380°C and a welding speed of 2.5 m / min, so that the intersections formed between the membrane blocks are T-shaped;
[0056] (4) Testing the TPO geomembrane, new geomembrane and HDPE geomembrane welded in step (3), and marking and repairing the defective parts found until they are retested and qualified;
[0057] The novel geomembrane comprises a substrate layer and an anti-ultraviolet layer coated on the upper surface of the substrate layer, and the thickness ratio of the substrate layer to the anti-ultraviolet layer is 1:0.3;
[0058] The thickness ratio of the TPO geomembrane, the new geomembrane and the HDPE geomembrane is 1.5:1:1.2;
[0059] The novel geomembrane is prepared by the following method:
[0060] a. By weight, 18 parts of polyetheretherketone, 13 parts of polycarbonate, 10 parts of modified polyester fiber, 8 parts of boron nitride, 40 parts of high-density polyethylene, 28 parts of low-density polyethylene, 24 parts of linear low-density polyethylene, 20 parts of polyethylene and 15 parts of ethylene-octene copolymer were placed in a twin-screw extruder at a main engine speed of 55 rpm, and calendered after extrusion through a die at 175° C. to obtain a substrate layer;
[0061] b. Disperse nano-SiO2 in a mixed solution of distilled water and anhydrous ethanol (the volume ratio of the two is 9:1), then add 5% silane coupling agent KH560 and stir evenly to obtain a nano-SiO2 aqueous solution, dissolve polyvinyl alcohol in distilled water to obtain a polyvinyl alcohol aqueous solution, mix the polyvinyl alcohol aqueous solution and the nano-SiO2 aqueous solution, place in a water bath and stir for 30 minutes, then place in an ultrasonic water tank and ultrasonically disperse for 30 minutes, the weight ratio of nano-SiO2 to polyvinyl alcohol is 0.8:10, and after filtering, an anti-ultraviolet layer coating is obtained;
[0062] c. Apply the anti-ultraviolet coating on the upper surface of the substrate layer. The coating amount of the anti-ultraviolet coating on the upper surface of the substrate layer is 200g / m 2 , after drying, an anti-ultraviolet layer is formed to produce a new type of geomembrane;
[0063] In step a, the preparation method of the modified polyester fiber comprises the following steps:
[0064] S1, soaking the polyester fiber in anhydrous ethanol overnight, taking it out and drying it to obtain the pretreated polyester fiber;
[0065] S2, adding dopamine hydrochloride to Tris buffer and stirring evenly to prepare a dopamine solution with a concentration of 2 g / L, then soaking the pretreated polyester fiber in the dopamine solution overnight, taking it out, washing it with water, and drying it to obtain a preliminarily modified polyester fiber;
[0066] S3. Stir and mix the silane coupling agent KH560 and 95% ethanol in a volume ratio of 1:500 at 50°C for 2 hours, then add FeCl3 to disperse evenly, and then add the initially modified polyester fiber to soak for 2 hours. The weight of the silane coupling agent KH560 is 10% of the initially modified polyester fiber. Take it out, wash it with water, and dry it to obtain the modified polyester fiber.
[0067] Example 3
[0068] A new type of monorail extrusion welding process for geomembrane, including:
[0069] (1) The bottom surface of the reservoir is leveled to ensure that there are no impurities within a vertical depth of 25 mm, and then the bottom surface is dried to ensure that the moisture content of the bottom is 15%;
[0070] (2) According to the reservoir bottom conditions, cut the geomembrane into appropriate sizes, then lay the stretched geomembrane on the reservoir bottom surface and keep the overlap area flat;
[0071] (3) TPO geomembrane, new geomembrane and HDPE geomembrane are overlapped in sequence with a overlap width of 12 cm, and are welded by a monorail extrusion welder at a welding temperature of 420°C and a welding speed of 3 m / min, so that the intersections formed between the membrane blocks are T-shaped;
[0072] (4) Testing the TPO geomembrane, new geomembrane and HDPE geomembrane welded in step (3), and marking and repairing the defective parts found until they are retested and qualified;
[0073] The novel geomembrane comprises a substrate layer and an anti-ultraviolet layer coated on the upper surface of the substrate layer, and the thickness ratio of the substrate layer to the anti-ultraviolet layer is 1:0.5;
[0074] The thickness ratio of the TPO geomembrane, the new geomembrane and the HDPE geomembrane is 1.8:1:1.5;
[0075] The novel geomembrane is prepared by the following method:
[0076] a. By weight, 20 parts of polyetheretherketone, 16 parts of polycarbonate, 13 parts of modified polyester fiber, 11 parts of boron nitride, 45 parts of high-density polyethylene, 32 parts of low-density polyethylene, 27 parts of linear low-density polyethylene, 25 parts of polyethylene and 18 parts of ethylene-octene copolymer were placed in a twin-screw extruder at a main engine speed of 60 rpm, and calendered after extrusion through a die at 180° C. to obtain a substrate layer;
[0077] b. Disperse nano-SiO2 in a mixed solution of distilled water and anhydrous ethanol (the volume ratio of the two is 9:1), then add 7% silane coupling agent KH570 and stir evenly to obtain a nano-SiO2 aqueous solution, dissolve polyvinyl alcohol in distilled water to obtain a polyvinyl alcohol aqueous solution, mix the polyvinyl alcohol aqueous solution and the nano-SiO2 aqueous solution, place in a water bath and stir for 40 minutes, then place in an ultrasonic water tank and ultrasonically disperse for 20 minutes, the weight ratio of nano-SiO2 to polyvinyl alcohol is 1.2:10, and after filtering, an anti-ultraviolet layer coating is obtained;
[0078] c. Apply the anti-ultraviolet coating on the upper surface of the substrate layer. The coating amount of the anti-ultraviolet coating on the upper surface of the substrate layer is 250g / m 2 , after drying, an anti-ultraviolet layer is formed to produce a new type of geomembrane;
[0079] In step a, the preparation method of the modified polyester fiber comprises the following steps:
[0080] S1, soaking the polyester fiber in anhydrous ethanol overnight, taking it out and drying it to obtain the pretreated polyester fiber;
[0081] S2, adding dopamine hydrochloride to Tris buffer and stirring evenly to prepare a dopamine solution with a concentration of 3 g / L, then soaking the pretreated polyester fiber in the dopamine solution overnight, taking it out, washing it with water, and drying it to obtain a preliminarily modified polyester fiber;
[0082] S3. Stir and mix the silane coupling agent KH570 and 95% ethanol in a volume ratio of 1:600 at 60°C for 3 hours, then add FeCl3 to disperse evenly, and then add the preliminarily modified polyester fiber and soak for 3 hours. The weight of the silane coupling agent KH570 is 12% of the preliminarily modified polyester fiber. Take out, wash and dry to obtain the modified polyester fiber.
[0083] Example 4
[0084] The difference from Example 2 is that the thickness ratio of the substrate layer to the anti-ultraviolet layer is 1:0.01.
[0085] Example 5
[0086] The difference from Example 2 is that the thickness ratio of the TPO geomembrane, the new geomembrane and the HDPE geomembrane is 2.5:1:2.
[0087] Example 6
[0088] The difference from Example 2 is that the modified polyester fiber is replaced by polyester fiber, and the preparation method of the modified polyester fiber is not disclosed.
[0089] Example 7
[0090] The difference from Example 2 is that the preparation method of the modified polyester fiber comprises the following steps:
[0091] S1, soaking the polyester fiber in anhydrous ethanol overnight, taking it out and drying it to obtain the pretreated polyester fiber;
[0092] S2. Stir and mix silane coupling agent KH560 and 95% ethanol at a volume ratio of 1:500 at 50°C for 2 hours, then add the pretreated polyester fiber and soak it for 2 hours. The weight of the silane coupling agent KH560 is 10% of the pretreated polyester fiber. Take it out, wash it with water, and dry it to obtain modified polyester fiber.
[0093] Example 8
[0094] The difference from Example 2 is that the weight ratio of nano-SiO2 to polyvinyl alcohol is 3:10.
[0095] Comparative Example 1
[0096] The difference from Example 2 is that the upper surface of the substrate layer is not coated with an anti-ultraviolet layer, and the preparation method of the novel geomembrane does not include step b and step c.
[0097] Comparative Example 2
[0098] The difference from Example 2 is that the new geomembrane is prepared by the following method:
[0099] By weight, 5 parts of carbon black, 2 parts of antioxidant 619, 18 parts of polyetheretherketone, 13 parts of polycarbonate, 10 parts of modified polyester fiber, 8 parts of boron nitride, 40 parts of high-density polyethylene, 28 parts of low-density polyethylene, 24 parts of linear low-density polyethylene, 20 parts of polyethylene and 15 parts of ethylene-octene copolymer are placed in a twin-screw extruder with a main engine speed of 55 rpm. After extrusion through a die at 175°C, the extruder is calendered to obtain a new geomembrane.
[0100] The new geomembranes in the above-mentioned Examples 1-8 and Comparative Examples 1-2 were subjected to performance tests. The tensile strength and elongation at break of different samples were tested according to CJ / T234-20066.6. The UV resistance of different samples was tested according to CJ / T234-20066.14. The retention of OIT at normal pressure after 1600 hours of ultraviolet irradiation was tested. The anti-seepage performance of different samples was tested according to CJ / T234-20066.16. Welded specimens with a size of 25 mm × 150 mm were cut, and the welded parts were subjected to tearing tests and shear tests using an Examo300F tensile testing machine. The peel strength and shear strength were both taken as the average values of the two seams. The results are shown in Table 1.
[0101] Table 1
[0102]
[0103]
[0104] It can be seen from the results in Table 1 that the monorail extrusion welding process of the new geomembrane of the present application is easy to construct. The new geomembrane adopted has both the excellent deformation adaptability of elastic materials and the weldability of plastic materials. It can provide a reliable anti-seepage barrier for the reservoir bottom, thereby protecting groundwater resources and the environment.
[0105] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.
Claims
1. A new type of monorail extrusion welding process for geomembrane, characterized in that: include: (1) The bottom surface of the reservoir is leveled to ensure that there are no impurities within a vertical depth of 20-25 mm, and then the bottom surface is dried to ensure that the moisture content of the bottom does not exceed 15%; (2) According to the reservoir bottom conditions, cut the geomembrane into appropriate sizes, then lay the stretched geomembrane on the reservoir bottom surface and keep the overlap area flat; (3) The TPO geomembrane, the new geomembrane and the HDPE geomembrane are overlapped in sequence and welded by a single-track extrusion welding machine so that the intersections formed between the membrane blocks are T-shaped; (4) Testing the TPO geomembrane, new geomembrane and HDPE geomembrane welded in step (3), and marking and repairing the defective parts found until they are retested and qualified; The novel geomembrane comprises a substrate layer and an anti-ultraviolet layer coated on the upper surface of the substrate layer, and the thickness ratio of the substrate layer to the anti-ultraviolet layer is 1:(0.1-0.5).
2. The monorail extrusion welding process of the novel geomembrane according to claim 1 is characterized in that: In step (3), the welding temperature is 350-420° C. and the welding speed is 2-3 m / min.
3. The monorail extrusion welding process of the novel geomembrane according to claim 1 is characterized in that: In step (3), the overlap width is 10-12 cm.
4. The monorail extrusion welding process of the novel geomembrane according to claim 1 is characterized in that: The thickness ratio of the TPO geomembrane, the new geomembrane and the HDPE geomembrane is (1-1.8):1:(1-1.5).
5. The monorail extrusion welding process of the novel geomembrane according to claim 1 is characterized in that: The novel geomembrane is prepared by the following method: a. By weight, 15-20 parts of polyetheretherketone, 10-16 parts of polycarbonate, 8-13 parts of modified polyester fiber, 6-11 parts of boron nitride, 30-45 parts of high-density polyethylene, 25-32 parts of low-density polyethylene, 20-27 parts of linear low-density polyethylene, 15-25 parts of polyethylene and 12-18 parts of ethylene-octene copolymer are placed in a twin-screw extruder at a main engine speed of 50-60 rpm, and calendered after extrusion through a die at 170-180° C. to obtain a substrate layer; b. Disperse nano-SiO2 in a mixed solution of distilled water and anhydrous ethanol, add 3-7% silane coupling agent and stir evenly to obtain a nano-SiO2 aqueous solution, dissolve polyvinyl alcohol in distilled water to obtain a polyvinyl alcohol aqueous solution, mix the polyvinyl alcohol aqueous solution and the nano-SiO2 aqueous solution, place in a water bath and stir for 20-40 minutes, then place in an ultrasonic water tank and ultrasonically disperse for 20-40 minutes, and filter to obtain an anti-ultraviolet layer coating; c. Applying the anti-ultraviolet coating on the upper surface of the substrate layer to form an anti-ultraviolet layer after drying, thereby obtaining a new geomembrane.
6. The monorail extrusion welding process of the novel geomembrane according to claim 5 is characterized in that: In step b, the weight ratio of nano-SiO2 to polyvinyl alcohol is (0.5-1.2):
10.
7. The monorail extrusion welding process of the novel geomembrane according to claim 5 is characterized in that: In step c, the coating amount of the anti-ultraviolet coating on the upper surface of the substrate layer is 180-250g / m 2 .
8. The monorail extrusion welding process of the novel geomembrane according to claim 5 is characterized in that: In step a, the preparation method of the modified polyester fiber comprises the following steps: S1, soaking the polyester fiber in anhydrous ethanol overnight, taking it out and drying it to obtain the pretreated polyester fiber; S2, adding dopamine hydrochloride to Tris buffer and stirring evenly to prepare a dopamine solution with a concentration of 1-3 g / L, then soaking the pretreated polyester fiber in the dopamine solution overnight, taking it out, washing it with water, and drying it to obtain a preliminarily modified polyester fiber; S3. Stir and mix silane coupling agent and ethanol in a volume ratio of 1:(400-600) at 40-60°C for 1-3h, then add FeCl3 to disperse evenly, then add the initially modified polyester fiber and soak for 1-3h, take out, wash with water, and dry to obtain the modified polyester fiber.
9. The monorail extrusion welding process of the novel geomembrane according to claim 8 is characterized in that: The silane coupling agent is selected from at least one of KH550, KH560 and KH570.
10. The monorail extrusion welding process of the novel geomembrane according to claim 8 is characterized in that: In step S3, the weight of the silane coupling agent is 8-12% of the initially modified polyester fiber.
Citation Information
Patent Citations
Apolyethylene composite geo-membraneand a preparation method thereof
CN109723090A
High-strength puncture-resistant geomembrane as well as preparation method and application thereof
CN112029185A
Geomembrane covering double-track hot melting technology process for refuse landfill
CN114211756A
HDPE geomembrane construction method
CN116556676A
Anti-seepage material for municipal engineering and preparation method of anti-seepage material
CN116787890A
Cited By
Water-resisting and salt-resisting composite geomembrane and preparation method thereof
CN120269904A
A water-proof and salt-blocking composite geomembrane and its preparation method
CN120269904B